2021
DOI: 10.3389/fphar.2021.664075
|View full text |Cite
|
Sign up to set email alerts
|

In silico Study of Trianthema portulacastrum Embedded Iron Oxide Nanoparticles on Glycogen Synthase Kinase-3β: A Possible Contributor to its Enhanced in vivo Wound Healing Potential

Abstract: Rich amount of phenolic compounds are available in Trianthema portulacastrum L. (TP) leaves and are traditionally utilized as a wound dressing material. Oxidative stress and inflammation affect the Wnt/β-catenin pathway by modulating the glycogen synthase kinase-3β (GSK) activity subjected to delay in wound healing. The objective of the current study was to explore the wound healing effect of ferric oxide nanoparticles biosynthesized with fractionated TP extract (FeTP). The ability of TP active components (pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…Taking into consideration that collagen is the major component strengthening and supporting extracellular tissue, we aimed to indirectly determine its content in skin tissue by determining hydroxyproline content [ 34 ]. Hydroxyproline permits the sharp twisting of the collagen helix, and high concentrations direct cell proliferation, as well as the synthesis, localization and maturation of collagen, all of which are in direct connection with the rate of wound healing [ 35 ]. A significant increase in hydroxyproline content in groups treated with H. italicum clearly suggests that the essential oil of H. italicum enhances collagen synthesis and deposition, which provides strength and tissue integrity, thereby playing a vital role in tissue epithelialization and homeostasis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into consideration that collagen is the major component strengthening and supporting extracellular tissue, we aimed to indirectly determine its content in skin tissue by determining hydroxyproline content [ 34 ]. Hydroxyproline permits the sharp twisting of the collagen helix, and high concentrations direct cell proliferation, as well as the synthesis, localization and maturation of collagen, all of which are in direct connection with the rate of wound healing [ 35 ]. A significant increase in hydroxyproline content in groups treated with H. italicum clearly suggests that the essential oil of H. italicum enhances collagen synthesis and deposition, which provides strength and tissue integrity, thereby playing a vital role in tissue epithelialization and homeostasis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result is comparable with earlier reports on chlorogenic acid, ferulic, and caffeic acid, which also showed greater affinity for glycogen synthase kinase 3. It can be suggested that acacetin-7-O-neohesperidoside might exhibit similar bioactivity to chlorogenic, ferulic, and caffeic acid [ 42 ]. In our study, acacetin-7-O-neohesperidoside has been identified as the main metabolite associated with the wound healing effect.…”
Section: Resultsmentioning
confidence: 99%
“…Before the docking study with the phytochemicals of H. sucuuba , protein files were retrieved from the PubChem database and protein data bank, respectively. Before performing molecular interaction studies, glycogen synthase kinase 3β [ 42 ] was further assessed for its missing side-chain residues using the openMM simulation tool ( accessed on 6 September 2021). Molecular docking studies were performed using Autodock v4.2.6.…”
Section: Methodsmentioning
confidence: 99%
“…İyileşme aşamalarını değerlendirmek için çeşitli matematiksel denklemler kullanılmaktadır. 53,54 İn Vİtro İn vitro modeller, skar oluşumu patogenezini ve iyileşme süreçlerini anlamak için kullanılır, ancak skar tedavileri için kullanılmaz. Günümüzde 3 ana model kullanılmaktadır.…”
Section: İn Si̇li̇counclassified